Simulation environment for the C14-experiment - Sarala, Roope (2016)
In this thesis, a simulation environment utilizing Geant4 simulation toolkit was constructed to study the C14 experiment located at the Pyhäsalmi Mine, Finland. The C14 experiment aims to find a liquid scintillator sample with the least amount of 14C, the radioactive isotope of carbon, with concentration preferably less than 10^-18. The scintillator detector used in the experiment consists of a 1.6 liter cylindrical vessel filled with liquid scintillator, two 20 cm conical light guides connected to the ends of the vessel and two low-background photomultiplier tubes to detect scintillator light. In addition, the detector is covered with a reflecting foil. The simulation environment was used to study the energy resolution and intrinsic background of the detector. The energy resolution of the experiment was simulated for electrons and alpha particles of energies 0-2 MeV (electron) and 3-10 MeV (alpha particle), which well cover the b-decay energy range of 14C. In the absence foil, the energy spectrum was highly position-dependent as particles originating near the edges of the vessel yielded more light than particles in the center. As a result, the energy resolution was worse without the foil. The most prominent source of intrinsic background was gamma rays from the photomultiplier tubes. The liquid bulk consisting of linear alkyl benzene did not cause a noticeable background unless the 222Rn concentration was of the order of 1 Bq/m3 but even still the gamma rays were dominant.